Implementation of Food Safety for Halal Food Smes: A Case Study of Fish Crackers - Sartono; Raden Hernadi; Devi Nadia (Green Publisher Indonesia, 2026)
Food safety is an important aspect in supporting the sustainability and competitiveness of halal food Micro, Small, and Medium Enterprises (MSMEs). The implementation of halal certification policies in Indonesia requires MSMEs to ensure that their production processes comply with food safety standards. However, many small-scale food producers still face challenges in identifying potential hazards and implementing systematic food safety controls. Therefore, this study aims to analyze the implementation of food safety through hazard identification and the determination of critical control points using the Hazard Analysis and Critical Control Point (HACCP) method in fish cracker MSMEs in Tangerang, Indonesia. This research employed a qualitative descriptive approach by applying HACCP principles through observation of the production process, interviews with business owners, and expert questionnaires. The stages of HACCP implementation included product description, process flow verification, hazard analysis, determination of critical control points (CCPs), monitoring systems, corrective actions, and documentation procedures. The results indicate that potential hazards in fish cracker production consist of biological and physical hazards, such as microbial contamination, dust, and environmental pollution. Three main critical control points were identified, namely the boiling, cooling and storage, and drying processes. Preventive measures include boiling at a minimum temperature of 80°C for 20 minutes, storage at −5°C to −10°C, and drying using protective nets. In conclusion, the application of HACCP provides an effective framework for identifying hazards and improving food safety management in halal food MSMEs, thereby supporting product quality, consumer protection, and the sustainability of the halal food industry.